Implementación de un sistema georreferenciado para contenedores de exportación - Bravo Retto, Saúl Fernando (2015)
The introduction and establishment of new security norms and trade facilitation measures are starting to being accepted all around the world. They have contributed to reinforce the cooperation and mutual understanding between several organisms of the public and private sector that are involved in the logistic chain. Nowadays the majority of companies attached to international trade are on a constant search to have the systems that will allow having a better control over their operations…….